Potential of carvacrol as plant growth-promotor and green fungicide against fusarium wilt disease of perennial ryegrass - Saghrouchni, Hamza; Barnossi, Azeddin El; Mssillou, Ibrahim; Lavkor, Isilay; Ay, Tahsin; Kara, Mohammed; Alarfaj, Abdullah A.; Hirad, Abdurahman Hajinur; Nafidi, Hiba-Allah; Bourhia, Mohammed; Var, Isil (Frontiers in Plant Science, 2023)
Perennial ryegrass (Lolium perenne L.) is a valuable forage and soil stabilisation crop. Perennial crops have long been associated with good environmental performance and ecosystem stability. Vascular wilt diseases caused by Fusarium species are the most damaging plant diseases affecting both woody perennials and annual crops. Therefore, the aim of the present study was the assessment of the preventive and growth-promoting effects of carvacrol against Fusarium oxysporum, F. solani, and F. nivale (phylogenetically analyzed on the basis of internal transcribed spacer (ITS) regions) causing vascular wilt of ryegrass in vitro and under greenhouse conditions. To accomplish this aim, various parameters were monitored including coleoptile development, rhizogenesis, the incidence of coleoptile lesions, disease index, the visual appearance of ryegrass health, ryegrass organic matter and soil fungal load. The results obtained showed that F. nivale was highly harmful to ryegrass seedlings compared to other Fusarium species. Furthermore, carvacrol with 0.1 and 0.2 mg/mL protected significantly the seedlings against Fusarium wilt diseases both in vitro and in the greenhouse. Simultaneously, carvacrol also functioned as a seedling growth promoter, as is reflected in all monitored parameters, such as the recovery of seedling height and root length, and the development of new leaf buds and secondary roots. Carvacrol proved to be effective plant growth promoter and a bio-fungicide against Fusarium vascular diseases.